Evaluation Of Liver Enzymes Activities (ALT-AST-ALP-GGT) Before And After Isoflurane Anesthesia In Neurosurgery Patients - Ladan Hosseini Gohari; Zahra Bangale; Mohammad Reza Fayazi; Farzaneh Moghaddam; Kamran Jamshidi (Tehran University of Medical Sciences, 2014)
Background and Aim: Isoflurane is one of the selective and mostly-used respiratory anesthetic materials in the field of neurosurgery. Studies have shown that temporary rise in the level of liver enzymes may occur after anesthesia by halogenic ethers and hence cause liver lesions. The aim of this study was to investigate the effects of isoflurane on the activity of ALT-AST-ALP-GGT enzymes as an indicator of liver function. Materials and Methods: This study was performed on a sample of 40 patients who were under neurosurgery without any liver disease in Milad Hospital of Tehran. The patients' blood samples were collected before, 24, and 72 hours after anesthesia. The enzymes activities was assessed by spectrophotometric method. Results: Insignificant changes before and after anesthesia were seen in the activity of ALP, and AST enzymes. The level of ALT enzyme has a significant rise, 72 (P=0/022) and 24 (P=0/014) hours after anesthesia in comparison with before anesthesia. The level of GGT enzyme in comparison to its past has significant rise 72 hours after anesthesia (P=0/002). The level of this enzyme showed a significant difference 24, and 72 hours after anesthesia (P=0/041). Conclusion: The significant changes seen in the levels of ALT, GGT enzymes in three different periods of time might be as a result of possible liver parenchymal and cholestatic damage caused by using Isoflurane or other drugs such as Midazolam which effects liver function. It seems the assessment of the levels of these enzymes can provide useful information for probable subsequent actions.